(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
Scalp burns are uncommon and rare. When they occur, they are usually caused by high electrical voltage. Reconstruction of scalp defects due to electrical burns is difficult, in part due to the extent of the defect, poor tissue mobility, and lack of certain resources. An unconventional technique was performed for coverage since it was accompanied by loss of bone tissue. A 66- year-old male patient is presented, who arrives at the emergency area of the Guayaquil “Abel Gilgert Pontón” Hospital because he suffered injuries from high-voltage electrical burns. He received the corresponding medical-surgical treatment, debridement of necrotic tissue on the scalp and exceresis of the biparietal bone table, leaving the medial area reamed and then placing foot grafts. In this way, the tissue defect at the scalp level can be resolved with tissue expanders. An adequate aesthetic result was not achieved since the patient refused to complete it.